Keutamaan Ilmu dalam Al-Qur’an dan Hadits : Perspektif Kitab Mahfudzot Fadhoilun Nabi wa Shahabat dalam Membangun Karakter Mahasiswa Universitas Islam Zainul Hasan Genggong Probolinggo - Sri Idhom Utami; Ainur Rofiq Sofa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This research investigates the significance of knowledge as presented in the Qur'an and Hadith, focusing on the Mahfudzot Fadhoilun Nabi wa Shahabat as a framework for understanding its role in shaping the character of students at Universitas Islam Zainul Hasan Genggong Probolinggo. The study examines how the Qur'anic and Hadith perspectives on knowledge emphasize moral, intellectual, and spiritual development and how these teachings can be applied to enhance the character of university students. By analyzing the implementation of these teachings within the academic and social environments, this research explores how knowledge, within the Islamic context, contributes to the development of ethical and responsible individuals. The findings are expected to offer valuable insights into the integration of Islamic values in higher education and their impact on the formation of student character.